Impact of Weather Insurance on Small Scale Farmers: A Natural Experiment - Marcela Ibanez; Stephan Dietrich (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper explores the impacts of traditional agricultural insurance that offers protection against climatic shocks on small-scale tobacco farmers in Colombia after a period of substantial crop failures. Our identi cation strategy bene ts from a natural experimental setup of the form in which the insurance was launched. We fnd that tobacco producers with access to the insurance program were less likely to acquire informal loans, were less likely to use loans to repay debts, and had access to loans with lower interest rates and longer maturation periods. Moreover, access to this program was positively associated with increased savings and accumulation of liquid assets.
Keywords: G22; O13; O12; 330